Association Between Vitamins and Amyotrophic Lateral Sclerosis: A Center-Based Survey in Mainland China - Wang, Mengli; Liu, Zhen; Sun, Weining; Yuan, Yanchun; Jiao, Bin; Zhang, Xuewei; Shen, Lu; Jiang, Hong; Xia, Kun; Tang, Beisha; Wang, Junling (Frontiers in Neurology, 2020)
To date, conflicting results about the role of vitamins in amyotrophic lateral sclerosis (ALS) have been reported along with a lack of systematic studies on all types of serum vitamins in patients with ALS. Moreover, extensive studies have been conducted on vitamins in other neurodegenerative diseases; however, whether serum vitamin alterations in ALS are similar to those in other neurodegenerative diseases remains unclear. Therefore, we performed a study involving a large Chinese cohort of patients with ALS to address this gap. In this study, 202 patients with ALS, 214 with a neurodegenerative disease that mimicked ALS (mimics), and 208 healthy controls were enrolled. Serum vitamins of all subjects were examined under fasting state in Clinical Laboratory. As a result, we found that higher vitamin A and E levels and lower vitamin B2, B9, and C levels were in patients with ALS compared to healthy controls, and that high vitamin A and E levels, and low vitamin B2, B9, and C levels were associated with an increased risk for ALS. In addition, serum vitamin C were lower in early-onset ALS patients compared to those in late-onset ALS patients; however, there was no significant correlation between serum vitamins and age at onset, sites at onset, disease duration, or disease severity of ALS. We also found that patients with ALS showed similar vitamin alterations to mimics, with the exception of vitamin E. In summary, our study adds information to the literature on the role of vitamins in ALS and provides support for clinical guidance regarding dietary changes and vitamin supplements in patients with ALS.